2019
DOI: 10.1016/j.bpj.2019.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Glioma Cell Migration Dynamics in Brain Tissue Assessed by Multimodal Optical Imaging

Abstract: Glioblastoma is a primary malignant brain tumor characterized by highly infiltrative glioma cells. Vasculature and white matter tracts are considered to be the preferred and fastest routes for glioma invasion through brain tissue. In this study, we systematically quantified the routes and motility of the U251 human glioblastoma cell line in mouse brain slices by multimodal imaging. Specifically, we used polarization-sensitive optical coherence tomography to delineate nerve fiber tracts while confocal fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…Regardless of the mechanism, recapitulating the behavior of cells in the channels is sensitive to the value of ψ pol , an effect that is not required for simulations of cells on 2D substrates using the same physical model of migration ( 9 ). This confinement-induced polarity may play a role in tumor progression by biasing cell movements away from the tumor bulk and into healthy tissue, as individual glioma cells are often observed migrating away from tumors in ex vivo slice cultures ( 11 , 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the mechanism, recapitulating the behavior of cells in the channels is sensitive to the value of ψ pol , an effect that is not required for simulations of cells on 2D substrates using the same physical model of migration ( 9 ). This confinement-induced polarity may play a role in tumor progression by biasing cell movements away from the tumor bulk and into healthy tissue, as individual glioma cells are often observed migrating away from tumors in ex vivo slice cultures ( 11 , 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Building upon an established motor-clutch model for cell traction ( 6 , 7 , 8 ), a recently developed computational cell migration simulator (CMS) reproduces the characteristic random motility of glioma cells on compliant hydrogels ( 9 , 10 ). Further studies reproduced glioma cell migration behaviors in environments with varying adhesiveness ( 11 ) and complex fiber orientation ( 12 , 13 ) by changing relevant environmental parameters. However, these studies did not consider the mechanical confinement encountered by invading glioma cells as they escape the tumor bulk ( 14 ) and encounter an ECM composed of hyaluronic acid and densely packed cells ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 95%
“…GBM cells have been generally described to spread to the surrounding brain tissues using the perivascular space around blood vessels and axons [17]; however, details concerning their selection algorithms for different routes as much as the existence of other strategies are still not fully understood. Using various types of cultures and fluorescent imaging, several research groups have demonstrated that malignant cells in GBM migrate individually, using the mesenchymal mode of cell migration and invasion [18][19][20]. Molecularly, this motile activity is associated with changes in cell polarity, actin polymerization and organization (see above) and results from differential expression and activity of small Rho GTPases Rac1, Cdc42, Rho and their targets [21][22][23], although their mutual interactions are still a matter of intensive scientific inquiry.…”
Section: Cytoskeleton Of Astrocytes and Malignant Gbm Cellsmentioning
confidence: 99%
“…Both structural and functional information about the specimen can be extracted from the OCT signal. [123][124][125][126][127][128] There are two major types of OCT systems commercially available on the market: SD and swept-source (SS). SDOCT is based on a broadband light source, typically super luminescent diode (SLD) and spectroscopic device to perform parallel (relative to wave-number) detection of the interference signal in a frequency domain.…”
Section: Optical Coherence Tomography For In Vivo Imaging Of Meningeamentioning
confidence: 99%